Rhynconema subsetosa, a new species of marine nematode, with a note on the genus Phylolaimus Murphy, 1963 - Murphy, D. G. (Proc. helminth. Soc. Wash., 1964)
Locality: ; Cabinet:
NeMys doc_id: 5128 NeMys doc_id: 6524